2014
DOI: 10.5558/tfc2014-034
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of biomass allocation in an age-sequence of secondary Pinus bungeana forests in China

Abstract: Tree biomass was investigated in an age-sequence of secondary lacebark pine (Pinus bungeana) forests to understand biomass partitioning patterns during stand development. Mean biomass of each tree component increased steadily as stands aged. Average growth rates and ratios of tree biomass to stand age increased with age. The ratio of below-to above-ground biomass remained relatively constant independent of stand age. Compared to DBH-H allometric equations, the DBH-only equations performed slightly better and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…A number of previous studies demonstrated that power function allometric equations based on DBH or squared DBH multiplied by H can be used to estimate tree biomass [29,35]. Allometric equations based on DBH are recommended because the measurement of H is time-consuming and less accurate than DBH [19,34,40,41].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A number of previous studies demonstrated that power function allometric equations based on DBH or squared DBH multiplied by H can be used to estimate tree biomass [29,35]. Allometric equations based on DBH are recommended because the measurement of H is time-consuming and less accurate than DBH [19,34,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…The highest percentage was 73% for four Mediterranean oak forests in Spain [19]. The proportion of stem to total tree biomass has been used to infer the light conditions, soil nutrient and age stage at study sites [35,36]. For example, the ratios in Chinese pine were 46.9%, 72.2%, 70.6% and 70.7% for young, middle-aged, immature, and mature stands, respectively [34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4). According to the biomass equation Y = 0.232 × DBH 2.247 for lacebark pine (Li et al 2014) and carbon concentrations with a mean value of 0.5 (Li et al 2013), biomass and carbon storage at different DBHs (10.0 cm, 20.0 cm, 30.0 cm, 40.0 cm and 50.0 cm) may be predicted. As temperatures rise, biomass and carbon storage significantly increase (Table 3).…”
Section: Tree-ring Climatic Responsementioning
confidence: 99%